Understanding Interfaith Marriage: A Multidisciplinary Perspective - Anisa, Lina Nur (Al-Syakhsiyyah: Journal of Law & Family Studies, 2024)
Interfaith marriage is a phenomenon increasingly observed both in Indonesia and globally. This trend reflects broader social changes such as globalization, increased mobility, and greater cultural exchange. Although common, interfaith marriages present unique challenges that require comprehensive understanding from a multidisciplinary perspective. This research aims to explore interfaith marriage through theological, psychological, and sociological lenses to provide a holistic analysis of its complexities. The research approach is qualitative, utilizing library research involving the study or review of books and literature related to the topic discussed. The data collection technique used in this study is documentation. The data analysis techniques applied are content analysis, induction, and deduction. The findings of this study reveal that successful integration of religious identities in interfaith marriages involves open communication, mutual respect, and active engagement in the community. This study emphasizes the importance of supportive legal frameworks and educational initiatives in promoting social acceptance. These insights offer practical implications for interfaith couples, counselors, and policymakers, providing guidance for navigating the challenges of interfaith marriage and building harmonious relationships. By understanding the theological, psychological, and sociological dimensions of interfaith marriage, stakeholders can better support these unions and promote inclusive and respectful social norms.